Developing and implementing linked electronic medical record and administrative data in primary care practice for diabetes in Alberta. (2018) - Drummond, Neil; Taylor, Matt; Garies, Stephanie; Shaw, Marta; Soos, Boglarka; Cummings, Michael; Forst, Brian; Yaraee, John; Cook, Lisa
No abstract available